2017
DOI: 10.12659/msm.898352
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ophthalmic Artery Branch Retrograde Intervention in the Treatment of Central Retinal Artery Occlusion (CRAO)

Abstract: BackgroundCentral retinal artery occlusion (CRAO) is the occlusion of the central retinal artery resulting in retinal infarction and acute vision loss. Digital subtraction angiography (DSA)–guided superselective ophthalmic artery or selective carotid thrombolysis remains the preferred treatment method for CRAO. This study aimed to evaluate the safety and clinical efficacy of the novel ophthalmic artery branch retrograde thrombolytic intervention for CRAO.Material/MethodsFifty patients with monocular CRAO were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Common treatments for CRAO are shown in Table 3. 3,[10][11][12][13][14][15][16][17][18] Ocular massage was performed because the embolus in the central retinal artery was expected to be dislodged. 3 As medical therapies, vasodilators such as nitroglycerine and anticoagulant such as heparin have been used; however, there is no evidence that these agents are effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common treatments for CRAO are shown in Table 3. 3,[10][11][12][13][14][15][16][17][18] Ocular massage was performed because the embolus in the central retinal artery was expected to be dislodged. 3 As medical therapies, vasodilators such as nitroglycerine and anticoagulant such as heparin have been used; however, there is no evidence that these agents are effective.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin was reversed with protamine at the end of the procedure A recent study showed that digital subtraction angiographyguided superselective ophthalmic artery or selective carotid thrombolysis with urokinase and papaverine was an effective treatment method for CRAO. 12 Another study showed that alprostadil infusion resulted in significant visual improvement in patients with CRAO. 11 In this study, the logarithm of the minimum angle of resolution best-corrected visual acuity significantly improved from 2.73 to 1.48 at 1 month after the onset of CRAO, and all six patients experienced vision improvement.…”
Section: F I G U R Ementioning
confidence: 99%
“…Common treatments for CRAO are shown in Table 3. 3,[10][11][12][13][14][15][16][17][18] Ocular massage was performed because the embolus in the central retinal artery was expected to be dislodged. 3 As medical therapies, vasodilators such as nitroglycerine and anticoagulant such as heparin have been used; however, there is no evidence that these agents are effective.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that digital subtraction angiographyguided superselective ophthalmic artery or selective carotid thrombolysis with urokinase and papaverine was an effective treatment method for CRAO. 12 Another study showed that alprostadil infusion resulted in significant visual improvement in patients with CRAO. 11 In this study, the logarithm of the minimum angle of resolution best corrected visual acuity significantly improved from 2.73 to 1.48 at 1 month after the onset of CRAO, and all 6 patients experienced vision improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A oxigenioterapia hiperbárica imediata tem sido usada para fornecer oxigênio à retina isquêmica, a fim de manter a viabilidade, enquanto outras modalidades de tratamento são aplicadas para restaurar o fluxo sanguíneo da artéria central da retina. A angiografia por subtração digital (artéria oftálmica superseletiva guiada ou trombólise selectiva da carótida) continua a ser o método de tratamento preferido para a oclusão de artéria central da retina 14 .…”
Section: Tratamentounclassified